Peran Mediasi Citra Merek terhadap Keputusan Pembelian Kosmetik Merek Lokal pada Wanita Urban - Selfia Irmayanti; Intan Tri Annisa (Universitas Medan Area, 2023)
This study aims to determine the effect of product quality, electronic word of mouth on purchasing decisions, as well as the role of mediating the image of local cosmetic brands in urban women. The sample in the study was 160 urban women in Indonesia who had bought local brand cosmetics. The sampling technique used was purposive sampling. Data was collected using a survey method with a questionnaire instrument. The data analysis method used is Partial Least Square Structural Equation Modeling (PLS-SEM) analysis. The results showed that product quality and electronic word of mouth had a positive and significant effect on brand image, electronic word of mouth and brand image had a positive and significant effect on purchasing decisions, product quality had a positive and insignificant effect on purchasing decisions, and brand image could mediate product quality and electronic word of mouth on purchasing decisions.